2020
DOI: 10.1002/hyp.13939
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use dominates climate controls on nitrogen and phosphorus export from managed and natural Nordic headwater catchments

Abstract: Agricultural, forestry-impacted and natural catchments are all vectors of nutrient loading in the Nordic countries. Here, we present concentrations and fluxes of total nitrogen (totN) and phosphorus (totP) from 69 Nordic headwater catchments (Denmark: 12, Finland:18, Norway:17, Sweden:22) between 2000 and 2018. Catchments span the range of Nordic climatic and environmental conditions and include natural sites and sites impacted by agricultural and forest management. Concentrations and fluxes of totN and totP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 100 publications
1
8
0
Order By: Relevance
“…Recent evidence suggests that in addition to atmospheric S and N deposition, climate and land use change are becoming increasingly important drivers of changes in boreal lake chemistry: lake browning (De Wit et al., 2016) and nutrient concentrations (N, phosphorus (P)) appear to be controlled by air pollution, land use, and climate (De Wit et al., 2020; Fölster et al., 2014; Vuorenmaa et al., 2018). Afforestation and increased terrestrial productivity have been suggested as a driver of browning in an 80‐year record of DOC (Skerlep et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that in addition to atmospheric S and N deposition, climate and land use change are becoming increasingly important drivers of changes in boreal lake chemistry: lake browning (De Wit et al., 2016) and nutrient concentrations (N, phosphorus (P)) appear to be controlled by air pollution, land use, and climate (De Wit et al., 2020; Fölster et al., 2014; Vuorenmaa et al., 2018). Afforestation and increased terrestrial productivity have been suggested as a driver of browning in an 80‐year record of DOC (Skerlep et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient loading to headwater streams is influenced by land cover in the surrounding catchments, as shown by studies in North America (Bosch et al, 2020; Coote et al, 1982; Dodds & Oakes, 2006), Europe and Scandinavia (Aguilera et al, 2012; de Wit et al, 2020). Previous studies of nutrient loading to headwater streams in agriculture‐dominated catchments have examined the influence of various agricultural practices and soil types.…”
Section: Introductionmentioning
confidence: 96%
“…Reduced supply from the catchment can be related to lower external inputs or greater terrestrial retention. At local (catchment) scales, oligotrophication can be connected to reductions in nutrient supply through, e.g., changes in land use 15 , control of point sources 2,5 , changes in internal cycling 3 and increased retention in upstream water bodies 8 . At regional scales, candidate drivers of oligotrophication include climate change, surface water browning and recovery from acidi cation.…”
Section: Introductionmentioning
confidence: 99%